Statement by the Managing Director on the Independent Evaluation Office Report on Growth and Adjustment in IMF-Supported Programs. (Policy Papers; Policy Paper, 2021)
Statement by the Managing Director on the Independent Evaluation Office Report on Growth and Adjustment in IMF-Supported Programs.